Large Acene Derivatives with B-N Lewis Pair Doping: Synthesis, Characterization, and Application - Zhang, Jin-Jiang; Ma, Ji; Liu, Fupin; Cui, Lin-Song; Fu, Yubin; Yang, Lin; Popov, Alexey A.; Weigand, Jan J.; Liu, Junzhi; Feng, Xinliang (Organic Letters, 2022)
Here, we report the synthesis of a novel class of B-N Lewis pair (LPB/N)-doped large acene derivatives (1a-1d) from the well-designed phenanthridine-based precursors. The resultant LPB/N-doped benzo-tetracene (1a), dibenzo-heptacene (1b), dibenzo-octacene (1c), and V-shaped tribenzo-nonacene (1d) are thoroughly characterized by X-ray crystallography, cyclic voltammetry, UV-vis absorption, and fluorescence spectroscopies together with DFT calculations. As a proof of concept, a 1a-based organic light-emitting diode device is fabricated to demonstrate the promising application in organic optoelectronics.
CRIS-Team Scopus Importer:2023-03-20